Investigation at the dawn of modernity (Academic Journal of Internal Affairs, 2015)
Using contemporary literature and archive documents, the author presents homicide cases from Pécs-Baranya, Hungary around 1870.
Keywords: homicide cases; Pécs-Baranya; 1870